Avaliação da unidade analítica na detecção de Salmonella spp. em frangos varejo - Yamatogi, Ricardo Seiti [UNESP]; Galvão, Julia Arantes [UNESP]; Baldini, Eduardo Delbon [UNESP]; Souza Júnior, Luiz Carlos Teixeira de [UNESP]; Rodrigues, Marianna Vaz [UNESP]; Pinto, José Paes de Almeida Nogueira [UNESP] (My University, 2011)
Over 95 % of the cases of human salmonellosis are foodborne. Among the foods involved in transmission of these diseases are the products from animal origin, being the poultry products highly relevant. To deal with this issue, the Ministry of Agriculture, Livestocks Farming and Supply (MAPA – Ministério da Agricultura, Pecuária e Abastecimento) established a program, in order to monitor the contamination by Salmonella spp. in poultry carcasses. This study aimed at comparing the efficiency of two analytical methodologies (rinsing of chicken carcass and skin excision) for recovering the cells from this bacterium and to verify the occurrence of this pathogen in samples collected in Botucatu, SP. Analyzing 100 carcasses, and computing the results by both techniques, contamination by Salmonella spp. was detected in 43% samples. Using the rinsing technique, 81.40% (35/43) showed positive results as well as 51.16% (22/43) using the skin excision methodology. Although the rinsing technique detected high number of positive samples, no statistical difference (p > 0.05) was found between the results obtained from two methodologies. Further studies should be conducted on this issue as the poultry carcasses are crucial source for transmission of Salmonella spp., and the subsequent introduction of this pathogen on food preparation environment.

Mais de 95% das salmoneloses humanas são de origem alimentar e, entre os alimentos envolvidos na transmissão estão os produtos de origem animal, especialmente os de maior relevância, os produtos avícolas. Diante desta questão, o Ministério de Agricultura, Pecuária e Abastecimento (MAPA) estabeleceu um programa com a finalidade de reduzir e monitorar a contaminação por Salmonella spp. nas carcaças de aves. Neste estudo, foi comparada a eficiência de duas metodologias de análises (o enxágue da carcaça e a excisão da pele) para recuperação de células da bactéria, bem como para a verificação da ocorrência do agente patogênico em amostras coletadas na região de Botucatu, SP. Em 100 carcaças analisadas, computando-se os resultados de ambas as metodologias, 43% (43/100) estavam contaminadas por Salmonella spp. Por meio de metodologia de enxágue foram detectadas 81,40% (35/43) amostras com resultados positivos e 51,16% (22/43) pela técnica de excisão. Embora a técnica de enxague tenha detectado número superior de amostras positivas, não houve diferença estatística (p > 0,05) entre os resultados obtidos pelas duas metodologias. Estudos adicionais devem ser realizados, dada à importância das carcaças de frango na veiculação de Salmonella spp. e sua consequente introdução no ambiente de preparação de alimentos.
Evaluation of the analytical unit for detecting Salmonella spp. in poultry at retail
Keywords: Salmonella; Poultry carcass; Rinsing; 25 grams excision; Salmonella; Carcaça de frango; Enxágue; Excisão de 25 gramas